2011
DOI: 10.1097/ccm.0b013e3181ffdd2f
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mortality resulting from a multicomponent intervention in a tertiary care medical intensive care unit

Abstract: Objective To evaluate whether a multicomponent intervention, particularly increasing staff, can achieve reductions in patient mortality in an already high-intensity, Leapfrog-compliant medical intensive care unit. Design Retrospective, observational study. Setting Medical intensive care unit of a tertiary care, academic medical center. Patients A total of 1,263 patients admitted between April 19, 2004 and April 18, 2006 (before the organizational change) were compared with 2,424 patients admitted between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 73 publications
2
21
0
2
Order By: Relevance
“…Previous analysis of the MICU patient population pre-and post-intervention showed that the case mix remained stable over the entire period studied. 12 Our study does have certain limitations. Although we found no difference between the 2 groups with regard to illness severity and comorbidities using the Case Mix Index and Charlson score, respectively, and no difference between the 2 groups of mechanically ventilated patients with regard to primary diagnosis, residual confounding may still have occurred, which is possible in quasi-experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous analysis of the MICU patient population pre-and post-intervention showed that the case mix remained stable over the entire period studied. 12 Our study does have certain limitations. Although we found no difference between the 2 groups with regard to illness severity and comorbidities using the Case Mix Index and Charlson score, respectively, and no difference between the 2 groups of mechanically ventilated patients with regard to primary diagnosis, residual confounding may still have occurred, which is possible in quasi-experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…These included the implementation of a 24-hour in-house intensivist and the addition of a clinical pharmacist to the care team. 15 It is difficult to isolate their relative contribution to the overall change in resource utilization, though we believe that it was the combination of these that maximized the benefit of the RT intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In California, the minimum staffing levels for direct care nurses are mandated and thus must be consistent on weekends and nights, None of the cited studies demonstrating care disparities on nights and weekends were able to correlate outcome differences to staffing levels, whether for nurses or physician providers. [3][4][5][6]9 Pharmacists and therapists have been shown to improve care as part of multidisciplinary care teams, [12][13][14][15][16] though a relationship between ancillary staffing levels and patient outcomes has not been well studied. Other hospital personnel critical to the delivery of care such as radiology technicians may be more lightly staffed on weekends and nights, potentially delaying needed imaging and increasing the length of hospital stay.…”
mentioning
confidence: 99%